2018
DOI: 10.1016/j.jtho.2017.11.126
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evidence for Combined Use of Aromatase Inhibitors and NSAIDs as Preventive Agents of Tobacco-Induced Lung Cancer

Abstract: Our results suggest a benefit to joint targeting of the estrogen and inflammatory pathways for NSCLC prevention. Combining AIs with nonsteroidal anti-inflammatory drugs reduces circulating E2, proinflammatory cytokines, and macrophage recruitment in the lung microenvironment after tobacco exposure. This strategy could be particularly effective in women who have underlying pulmonary inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Conversely, in NNK treated mice that received the aromatase inhibitor anastrozole, a significant reduction in pulmonary TAMs was found, which were found to be aromatase and ERβ positive (67). Addition of a non-steroidal anti-inflammatory agent to anastrozole was shown to further reduce TAM recruitment in this model (67). A limitation to the studies in the NNK model of lung cancer is that TAM expression was assessed through IHC and M1/M2 phenotypes were not distinguished.…”
Section: Estrogen Modulates Tumor Infiltrating Myeloid Cellsmentioning
confidence: 92%
See 3 more Smart Citations
“…Conversely, in NNK treated mice that received the aromatase inhibitor anastrozole, a significant reduction in pulmonary TAMs was found, which were found to be aromatase and ERβ positive (67). Addition of a non-steroidal anti-inflammatory agent to anastrozole was shown to further reduce TAM recruitment in this model (67). A limitation to the studies in the NNK model of lung cancer is that TAM expression was assessed through IHC and M1/M2 phenotypes were not distinguished.…”
Section: Estrogen Modulates Tumor Infiltrating Myeloid Cellsmentioning
confidence: 92%
“…In lung preneoplasias that developed after NNK plus E2 treatment, a significant increase in inflammatory markers and VEGF, an E2 reponsive gene and regulator of macrophage recruitment and the M1/M2 macropahge switch, was found compared to control (67). Conversely, in NNK treated mice that received the aromatase inhibitor anastrozole, a significant reduction in pulmonary TAMs was found, which were found to be aromatase and ERβ positive (67). Addition of a non-steroidal anti-inflammatory agent to anastrozole was shown to further reduce TAM recruitment in this model (67).…”
Section: Estrogen Modulates Tumor Infiltrating Myeloid Cellsmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, E2 enhanced M2 macrophage secretion of vascular endothelial growth factor (VEGF), an identified mediator of M2 macrophage recruitment [ 81 , 82 ]. E2 has been shown to also upregulate VEGF expression and pulmonary macrophage content in the lungs of mice exposed to a tobacco carcinogen [ 83 ]. Evaluation of E2-mediated tumor growth in a HGSOC murine model showed that E2 not only enhanced the growth of ER-negative xenografts, but also increased M2 TAM infiltration compared to untreated ovariectomized mice [ 54 ].…”
Section: Estrogen Receptor and Aromatase Expression And Estrogen-mmentioning
confidence: 99%